2015
DOI: 10.1159/000430337
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Residues in Angiotensin II Type 1 Receptor Sensing Mechanical Stretch and Function in Cardiomyocyte Hypertrophy

Abstract: Background/Aims: Angiotensin II (AngII) type 1 receptor (AT1R) could be activated by mechanical stress without the involvement of AngII during the development of cardiac hypertrophy. We aimed to identify sensing sites of AT1R for activation by mechanical stretch. Methods: We constructed several site-directed mutations of AT1R (AT1RK199Q, AT1RL212F, AT1RQ257A and AT1RC289A), transfected them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…Researchers in a previous study also reported that volume overload resulted in the cardiac hypertrophy . In addition, Jiang et al demonstrated that Ang II type 1 receptor was involved in the cardiomyocyte hypertrophy under mechanical stretch conditions . These studies are consistent with our observations that cardiac hypertrophy was induced by mechanical stress.…”
Section: Discussionsupporting
confidence: 92%
“…Researchers in a previous study also reported that volume overload resulted in the cardiac hypertrophy . In addition, Jiang et al demonstrated that Ang II type 1 receptor was involved in the cardiomyocyte hypertrophy under mechanical stretch conditions . These studies are consistent with our observations that cardiac hypertrophy was induced by mechanical stress.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have indicated that Ang II exerts direct effects on myocardial cells, including cardiomyocyte growth, accumulation of extracellular matrix and hypertrophy [33-35]. The prohypertrophic effect of Ang II was mediated by angiotensin type 1 receptor (AT1R), which was blocked to prevent cardiac hypertrophy [36].…”
Section: Discussionmentioning
confidence: 99%
“…The method of quantifying the level of gene expression was as previously described [10,11]. The RNA was reverse transcribed with oligo-dT and Superscript First-strand Synthesis System for RT-PCR (TaKaRa), The cDNA was then amplified using an iCycler (ABI) and the Brilliant SYBR Green QPCR master mix (TaKaRa) withβ-actin as an internal control.…”
Section: Real Time-pcr Analysismentioning
confidence: 99%